Survey of Open Educational Resources Among Undergraduates in a State University in Nigeria - Igbinovia, Magnus Osahon; Obinyan, Oluwatoyin; Okumode, Vincent (Ghana Library Journal, 2022)
The purpose of this study is to find out how well Ambrose Alli University, Ekpoma, undergraduates are aware of and utilise free educational materials. Consequently, four (4) study objectives were developed to address the amount of awareness, level of use, purpose, and challenges connected with students’ use of OERs. The study adopted a descriptive survey design for a target population of 8,501 undergraduates across three faculties (Arts, Education and Physical Sciences) in the university enrolled for the 2018/2019 academic session. The study employed Yamane (1967) sample size determination and stratified random sampling technique to arrive at a sample size of 250 undergraduates which was allocated proportionally across the three faculties. A structured questionnaire was used to elicit responses which were analysed using descriptive statistics of frequency, percentage, arithmetic mean and standard deviation. The result of the analysis revealed a low level of OERs awareness among the undergraduates. Also, the study showed a low level of use of OERs among the undergraduates. Majority of those who used OERs affirmed their purpose for use to be acquiring free and quality information resources and increase their knowledge in their area of study. Findings from the analysis also revealed that lack of awareness and lack of knowledge on how to use OERs were major challenges confronting the use of OERs among the undergraduates. The study conclusively noted that embracing the full potential of OERs pushes universities to critically reconsider their policies and strategies especially in the areas of awareness and use by undergraduates who are the key beneficiary of the open access initiative.